STRUKTUR PEREKONOMIAN BERDASARKAN PENDEKATAN SHIFT SHARE ARCELUS DALAM PENGEMBANGAN WILAYAH KABUPATEN KEBUMEN - Najah, Toifatun; Panjawa, Jihad Lukis (Jurnal Kajian Ekonomi dan Kebijakan Publik (JEpa), 2021)
Abstract:Kebumen Regency is one of the regencies in Central Java Province which is located on the South Coast and has many economic potentials. These potentials have not been optimally utilized for regional development, so regional development in Kebumen District has been delayed. The purpose of this study is to analyze the structure and shift of the economic sector in the development of Kebumen Regency. The data used in this study are secondary data. The analytical tool used is the Location Quetient analysis which consists of Static Location Quetient (SLQ,), Dynamic Location Quetient (DLQ), Arcelus Shift Share Analysis. The results of this study indicate that in Kebumen Regency the potential sectors that can be used as regional development are the Agriculture, the Forestry and Fisheries sector, the Manufacturing Industry sector and the Trade Sector. The sector has a fairly good influence in the development of Kebumen Regency. For Kebumen Regency, there has not been a complete shift in the structure of the economy, which is still based on the agricultural sector, but there have been indications that the industrial and trade sectors have developed quite well in the Kebumen district. With the identification of key sectors, it is expected to be able to encourage the development of the region to be more focused and able to improve the welfare of the community. Keywords: LQ, Arcelus Shift Share, leading sectors, regional development